How sure are you of your result? Put a number on it. (6th December 2018) - Goodman, Steven N.
Any scientist publishing a claim should quantify their confidence in it with a probability, argues Steven N. Goodman. Any scientist publishing a claim should quantify their confidence in it with a probability, argues Steven N. Goodman.